Avaliação de genótipos de sorgo forrageiro na zona da mata de Alagoas - Silva, Michel Lopes (2011)
This study was conducted at the Center for Agrarian Sciences, Federal University of Alagoas, Rio Largo-AL, the Zona da Mata, from July to November 2009 andaimed to evaluate the performance of 30 genotypes of sorghum subjected to water stress as productivity of green. The experimental design was a randomized block with two replications. After demarcation of the experiment was done plowing and disking after liming according to soil analysis recommendation. The experimental plots had dimensions of 3.2 x 6m (19.2 m2), consisting of four grooves. The seeds were scattered all along the furrow and covered with a thin layer of soil, and the useful area consisting of the two central rows. Seven days after sowing thinning proceeded to obtain a density of 12 plants per meter below the experimental area was fertilized. The material was collected at 105 days of vegetative growth, cut with a knife cutting height of about 5 cm of soil, being weighed on digital scales. At harvest were measured as height and stem diameter. 16 days after harvest was made an analysis of the percentage of regrowth of each genotype used. There was no significant difference at 5% probability by Scott and Knott, to yield variable (t/há-1) indicating that all genotypes survived the drought. Significant difference at 5% probability by Scott and Knott, both for height and stem diameter for the genotypes indicating that SF-25, 24Ca84-B1Ca87-B2SB88-BCa89, 22. Forager Chocolate Forager -25 thesis, dissertation Forager-33, T34 (Sudan 4202 R1) had greater heights compared to the others. Genotypes. SF-25, 03/01/2002, 43-70-02, 10-Ca84-B2Ca87-B2SB88-BCa89, 38-Ca84-B2Ca87-B2SB88-BCa89, Ca84-BCa87-B1SB88-BCa89, 41-Ca84 -BCa87-B1SB88-BCa89, Ca84-46-B2Ca87-B2SB88-BCa89, Ca84-68-BCa87-01SB88-01SB89, 10-Ca84-Ca89-B1Ca87-B1SB88, 24Ca84-B1Ca87-B2SB88-BCa89, 25Ca84-B1Ca87-B1SB88 -BCa89, 25Ca84-B2Ca87-B1SB88-BCa89, 52.Ca84-BCa87-B1SB88-BCa89, 63Ca84-B1Ca87-B2SB88-BCa89, ST87-18, ST88-01, ST89-01, ST91-13, B-VIT91, CA92 b, Forager black. Chocolate Forager, T14 (03.02.2001 R1), will present larger stem diameter. Significant difference at 5% by Scott and Knott indicating a higher percentage of regrowth in genotypes 10-Ca84-B2Ca87-B2SB88-BCa89; 25-Ca84-B2Ca87-B1SB88-BCa89; 41-Ca84-BCa87-B1SB88-BCa89 ; 46-Ca84-B2Ca87-B2SB88-BCa89; 68-Ca84-BCa87-01SB88-01SB89; 10-Ca84-Ca89-B1Ca87-B1SB88; 25Ca84-B1Ca87-B1SB88-BCa89; 25Ca84-B2Ca87-B1SB88-BCa89; 52.Ca84 -BCa87-B1SB88-BCa89; Forager thesis -25; Forager thesis-33-Araripina and Red Sorghum. There was no statistical difference between the genotypes for water use efficiency. There was no significant difference at 5% probability by Scott and Knott, for the variable dry matter, crude protein, NDF, ADF, hemicellulose and mobile content.